2009
DOI: 10.1029/2008tc002264
|View full text |Cite
|
Sign up to set email alerts
|

Localization of shear along a lithospheric strength discontinuity: Application of a continuous deformation model to the boundary between Tibet and the Tarim Basin

Abstract: A marked contrast in strength (or viscosity) within a continuously deforming zone can lead to concentration of shear strain in the weaker material adjacent to the boundary between them, but localization comparable to the width of the Altyn Tagh shear zone requires an additional weakening process. During numerical experiments on a thin viscous sheet indented by a rigid object, a shear zone develops adjacent to a strong region mimicking the Tarim Basin, when the boundary between the weak and strong regions is ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 85 publications
0
65
0
Order By: Relevance
“…), the Altyn Tagh Fault (ATF) is usually considered to be the largest active strike‐slip fault of Eurasia. Slip‐rate and seismic behavior of the fault are keys to the present‐day kinematics of collision tectonics in Asia, and viewed as an important factor in evaluating whether continental deformation can be approximated by block tectonics or not, a topic that remains the subject of debate [ Avouac et al , 1993; Calais et al , 2006; Dayem et al , 2009; England and Houseman , 1986; England and Molnar , 1997; Hilley et al , 2009; Holt et al , 2000; Loveless and Meade , 2011; Meade , 2007; Peltzer and Saucier , 1996; Thatcher , 2007; Vergnolle et al , 2007]. Recent slip‐rate estimates based on complementary and/or similar techniques currently yield disparate results along the Altyn Tagh Fault.…”
Section: Introductionmentioning
confidence: 99%
“…), the Altyn Tagh Fault (ATF) is usually considered to be the largest active strike‐slip fault of Eurasia. Slip‐rate and seismic behavior of the fault are keys to the present‐day kinematics of collision tectonics in Asia, and viewed as an important factor in evaluating whether continental deformation can be approximated by block tectonics or not, a topic that remains the subject of debate [ Avouac et al , 1993; Calais et al , 2006; Dayem et al , 2009; England and Houseman , 1986; England and Molnar , 1997; Hilley et al , 2009; Holt et al , 2000; Loveless and Meade , 2011; Meade , 2007; Peltzer and Saucier , 1996; Thatcher , 2007; Vergnolle et al , 2007]. Recent slip‐rate estimates based on complementary and/or similar techniques currently yield disparate results along the Altyn Tagh Fault.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming n = 5, a total horizontal stress 4η D xx = 350 MPa, a density difference between mantle lithosphere and water ρ = 2300 kg m −3 and H = 25 km yields α d ≈ 9, which is not sufficient for significant folding. However, if we assume that the mechanically competent (upper) region of the mantle lithosphere is deforming by low-temperature plasticity (Peierls creep), then the effective (or apparent) value of n is in the range 10-25 (Dayem et al, 2009;Schmalholz and Fletcher, 2011) and we get α d ≈ 19-47, a value sufficient for significant folding. Furthermore, if we assume that the competent level of the oceanic lithosphere is not overlain by water, but by unconsolidated sediments, then the density difference reduces to ρ = ∼ 1000 kg m −3 (Martinod and Molnar, 1995) and α d ≈ 43-107.…”
Section: Lithospheric Foldingmentioning
confidence: 99%
“…More recently, however, Dayem et al . [] found that the vertically integrated rheology of the lithosphere beneath the Altyn Tagh Fault zone on the Tibetan Plateau may be better described with a power‐law exponent even greater than 10. An inferred value of ≈ 3 suggests that most of the strength in deforming continental lithosphere lies in the part of the lithospheric mantle that deforms by creeping flow [ Sonder and England , ].…”
Section: Introductionmentioning
confidence: 99%
“…Because oceanic lithosphere has a much thinner crust and the mantle is generally more resistant to creeping flow, fracturing and faulting typically extend to greater depth in oceanic lithosphere and the relevant exponent may then be greater than 3. The vertically integrated constitutive law for the lithosphere combines the properties of the upper lithosphere, which deforms by faulting and fracturing and for which the appropriate power‐law exponent is n → ∞, and the lower lithosphere, which deforms by dislocation glide [ Goetze , ; Evans and Goetze , ; Raterron et al ., ; Dayem et al ., ; Mei et al ., ] and obeys an exponential law, and by dislocation creep, which obeys a power‐law with n ≈ 3 [ Kohlstedt et al ., ]. Although only the lowest layer obeys a power‐law, the integrated behavior of deforming lithosphere can be well approximated by a power‐law [ Sonder and England , ].…”
Section: Introductionmentioning
confidence: 99%